2015
DOI: 10.1002/jcph.450
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics, and pharmacodynamics of TV‐1380, a novel mutated butyrylcholinesterase treatment for cocaine addiction, after single and multiple intramuscular injections in healthy subjects

Abstract: Human plasma butyrylcholinesterase (BChE) contributes to cocaine metabolism and has been considered for use in treating cocaine addiction and cocaine overdose. TV-1380 is a recombinant protein composed of the mature form of human serum albumin fused at its amino terminus to the carboxy-terminus of a truncated and mutated BChE. In preclinical studies, TV-1380 has been shown to rapidly eliminate cocaine in the plasma thus forestalling entry of cocaine into the brain and heart. Two randomized, blinded phase I stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 33 publications
0
54
0
1
Order By: Relevance
“…9,18 Cocaine-degrading enzymes derived from human plasma butyrylcholinesterases (BChE) and bacterial cocaine esterases (CocE) have been tested for treatment of cocaine dependence and overdose (NCT01887366, and NCT01846681, Table 1). [148][149][150] These clinical studies showed no evidence of side effects, and provide proof of concept for enzyme-based SUD treatments. A detailed review of clinical studies of cocaine esterases can be found elsewhere.…”
Section: Enzymesmentioning
confidence: 93%
“…9,18 Cocaine-degrading enzymes derived from human plasma butyrylcholinesterases (BChE) and bacterial cocaine esterases (CocE) have been tested for treatment of cocaine dependence and overdose (NCT01887366, and NCT01846681, Table 1). [148][149][150] These clinical studies showed no evidence of side effects, and provide proof of concept for enzyme-based SUD treatments. A detailed review of clinical studies of cocaine esterases can be found elsewhere.…”
Section: Enzymesmentioning
confidence: 93%
“…This work is exciting to those involved in pharmacokinetic approaches to drug toxicity; such constructs promise to be the first drug-metabolizing enzymes used as therapeutic agents. The analog described (1) seems to be the third of its type; this analog is apparently the longest lasting in the series (2,3).…”
mentioning
confidence: 87%
“…CocH2 and CocH3 etc . were designed in our lab to improve the catalytic efficiency of human BChE against cocaine for treatment of cocaine addiction and overdose [23, 2632], and were not expected to improve the catalytic efficiency against ghrelin. Hence, it is not surprizing to know that CocH3 has a moderate catalytic efficiency ( k cat / K m = 4.8 × 10 5 min −1 M −1 ) against ghrelin compared to that ( k cat / K m = 6.1 × 10 5 min −1 M −1 ) of wild-type human BChE, and that CocH2 has a slightly lower catalytic efficiency ( k cat / K m = 2.2 × 10 5 min −1 M −1 ) against ghrelin [33].…”
Section: Introductionmentioning
confidence: 99%